CSC444 - Java Programming / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2023)
The course is designed to introduce students to intermediate level Java programming language and produce students who are able to solve extensive computer-based and web-based problems. It emphasizes various aspects of problem solving and develops application using GUI, Applet and web component technology.